Two-dimensional Length Extraction of Ballistic Target from ISAR Images Using a New Scaling Method by Affine Registration - Guanghu, Jin; Xunzhang, Gao; Zhen, Dong (Defence Science Journal, 2014)
The length of ballistic target is one of the most important features for target recognition. It can be extracted from ISAR Images. Unlike from the optical image, the length extraction from ISAR image has two difficulties. The first one is that it is hard to get the actual position of scattering centres by the traditional target extraction method. The second one is that the ISAR image’s cross scale is not known because of the target’s complex rotation. Here we propose two methods to solve these problems. Firstly, we use clustering method to get scattering centers. Secondly we propose to get cross scale of the ISAR images by affine registration. Experiments verified that our approach is realisable and has good performance. Defence Science Journal, Vol. 64, No. 5, September 2014, pp.458-463, DOI:http://dx.doi.org/10.14429/dsj.64.5001